Trial Germination of Coastal Vegetation (Terminalia catappa, Calophyllum inophylum L., and Barringtonia asiatica) in the Kima Atas Permanent Nursery - Suryawan, Ady; Asmadi, Nur; Mamonto, Rinna (Jurnal Wasian, 2014)
It was estimated that North Sulawesi needs 9,870,093.33 coastal vegetation seeds to rehabilitate the damage of coastal ecosystems which reach 14,805.14 ha, where the largest area 13.884 ha located in other land use. This study aims to provide information of seed germination techniques in Permanent Nursery Kima Atas, Manado. Research was arranged in complete randomized design as factorial with three replications. Ketapang (Terminalia cattapa) will obtain high viability in fluctuation of temperature and humidity, i.e used sand media, without wildlings and placed under 25% shade and rain. Keben (Baringtonia asiatica) through the incision and decay that placed in the open location will obtain viability until 90% within 2 months. Nyamplung (Calophyllum inophyllum) requires shell splitting in order to improve the viability and it can be done by cracking and stripping.